Strong Static Magnetic Fields Elicit Swimming Behaviors Consistent with Direct Vestibular Stimulation in Adult Zebrafish - Ward, Bryan K. (Public Library of Science, 2014)
Zebrafish (Danio rerio) offer advantages as model animals for studies of inner ear development, genetics and ototoxicity. However, traditional assessment of vestibular function in this species using the vestibulo-ocular reflex requires agar-immobilization of individual fish and specialized video, which are difficult and labor-intensive. We report that using a static magnetic field to directly stimulate the zebrafish labyrinth results in an efficient, quantitative behavioral assay in free-swimming fish. We recently observed that humans have sustained nystagmus in high strength magnetic fields, and we attributed this observation to magnetohydrodynamic forces acting on the labyrinths. Here, fish were individually introduced into the center of a vertical 11.7T magnetic field bore for 2-minute intervals, and their movements were tracked. To assess for heading preference relative to a magnetic field, fish were also placed in a horizontally oriented 4.7T magnet in infrared (IR) light. A sub-population was tested again in the magnet after gentamicin bath to ablate lateral line hair cell function. Free-swimming adult zebrafish exhibited markedly altered swimming behavior while in strong static magnetic fields, independent of vision or lateral line function. Two-thirds of fish showed increased swimming velocity or consistent looping/rolling behavior throughout exposure to a strong, vertically oriented magnetic field. Fish also demonstrated altered swimming behavior in a strong horizontally oriented field, demonstrating in most cases preferred swimming direction with respect to the field. These findings could be adapted for ‘high-throughput’ investigations of the effects of environmental manipulations as well as for changes that occur during development on vestibular function in zebrafish.